Esophageal Fully-Covered Metal Stent as a Rescue Therapy for a Strasberg Type A Biliary Leak in a Huge Common Bile Duct Dilation - Bisogni, Damiano; Talamucci, Luca; Rossi, Michele; Manetti, Roberto (Acta Biomedica Atenei Parmensis, 2023)
Treatment of biliary leaks is challenging and complex. Even if endoscopic sphincterotomy with biliary stenting is usually resolutive in restoring the original bile flow, common bile duct (CBD) diameter is crucial in defining the size and features of the stent. Additional factors, such as uncommon anatomical reconstructions due to a previous abdominal surgery, could make the endoscopic approach more difficult, therefore increasing the risk of failure. Many articles deal with uncommon technique adopted to allow an optimal healing of biliary leaks but, thus far, only two reports of biliary stent using an esophageal through-the-scope (TTS), partially-covered, self-expandable metal stent (SEMS) exist in the current literature. This article describes the deployment of an esophageal SEMS into the CBD for a refractory type A Strasberg fistula in a Billroth-II reconstruction. To our knowledge, this is the first report concerning the use of an esophageal stent for CBD drainage in a Billroth-II reconstruction.